1998
DOI: 10.1093/ps/77.12.1846
|View full text |Cite
|
Sign up to set email alerts
|

B-complex associated immunity to Salmonella enteritidis challenge in congenic chickens

Abstract: Six trials were conducted during which a total of 12 congenic lines (University of California-Davis, UCD) homozygous for various B-complex haplotypes, were challenged as neonates by intraperitoneal injection with either of two isolates of Salmonella enteritidis. Because these B haplotypes were expressed on a common genetic background (highly inbred Line UCD 003), and mortality differences among lines were statistically significant in three of the six trials, and morbidity (body weight) differences were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…The hypothesis used in this approach is that candidate genes represent a large proportion of the quantitative trait loci (QTL) that determine a particular trait. Over the past 20 years, several genes have been found to affect the immune response to SE in poultry [5,10,21,26]. The main objective of this study was to analyze new candidate genes for Salmonella response in poultry.…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis used in this approach is that candidate genes represent a large proportion of the quantitative trait loci (QTL) that determine a particular trait. Over the past 20 years, several genes have been found to affect the immune response to SE in poultry [5,10,21,26]. The main objective of this study was to analyze new candidate genes for Salmonella response in poultry.…”
Section: Introductionmentioning
confidence: 99%
“…Autoimmune disease associations with HLA are sometimes reported for alleles at individual loci, but with few exceptions it is difficult to understand whether individual loci or other genes nearby are actually responsible for the observed effect. In the chicken, MHC-B haplotypes, until recently distinguished primarily by serological methods, display strong influences in several infectious diseases (1)(2)(3)(4)(5). Resistance to Marek's disease tumors was mapped to a gene, or genes, closely linked to serologically-defined MHC-B class I (as opposed to BG Ags) in analyses of rMHC-B haplotypes (6 -8).…”
mentioning
confidence: 99%
“…This large QTL number supports the highly polygenetic nature of the host response, but QTLs with effects as large as 37% of the phenotypic variance in carrier state have been identified (111). Some QTLs are in regions known to contain immune-response genes, such as the MHC (111), or in regions in which previous studies have identified associations of gene SNPs with Salmonella-response phenotypes (82,83). Locations of QTLs have also been verified from experimental to commercial populations (115), which demonstrates the effectiveness of using experimental populations to identify QTLs of value in commercial application.…”
Section: Salmonellamentioning
confidence: 74%
“…A major biological candidate gene region, the MHC, was selected for investigation because of its association with many other disease-resistance traits. Once again, specialized experimental populations served as an effective target of study; B-complex (MHC) congenic lines revealed differences in mortality and morbidity after Salmonella challenge (82), and polymorphism in MHC class I genes was associated with other Salmonella-response traits in experimental line crosses (83,84).…”
Section: Salmonellamentioning
confidence: 99%